Some remarks on the stability analysis in Robe's three body problem - R. Meire (International Journal of Mathematics and Mathematical Sciences)
An improved technique is presented for the stability analysis of Robe's 3-body problem which gives more accurate results for the transition curves in the parameter plane than does Robe's paper.